2014
DOI: 10.1007/s13593-014-0231-8
|View full text |Cite
|
Sign up to set email alerts
|

DNA pyrosequencing evidence for large diversity differences between natural and managed coffee mycorrhizal fungal communities

Abstract: International audienceArabica coffee is a major agricultural commodity worldwide, representing 60 % of the world’s coffee production. Arabica coffee is cultivated in more than 36 countries and is a key cash crop for many developing countries. Despite the coffee’s huge economic importance, there is very limited knowledge on the association of arbuscular mycorrhizal fungi with coffee roots. Therefore, we assessed the mycorrhizal diversity and community composition in Arabica coffee (Coffea arabica L.), using 454… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 31 publications
(41 reference statements)
1
33
2
Order By: Relevance
“…About 14 % of N and 38 % of P inputs were leached to rivers, which leads to water quality problems, such as eutrophication. As well, De Beenhouwer et al (2015) reported a strong reduction of soil microorganism diversity in intensively managed coffee systems, where chemical fertilizers and pesticides are abundantly used.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…About 14 % of N and 38 % of P inputs were leached to rivers, which leads to water quality problems, such as eutrophication. As well, De Beenhouwer et al (2015) reported a strong reduction of soil microorganism diversity in intensively managed coffee systems, where chemical fertilizers and pesticides are abundantly used.…”
Section: Introductionmentioning
confidence: 97%
“…Coffee is the most intensively traded tropical agricultural commodity worldwide, cultivated in over 50 countries and covering more than 11 million ha (De Beenhouwer et al 2015). In Ecuador, coffee production has a great social, economic, and ecological importance because more than 4 % of the population directly relies on coffee production for their livelihoods; it is a primary source of foreign exchange for private producers and the State and it is part of the diverse agrosystems of the country.…”
Section: Introductionmentioning
confidence: 99%
“…Among various crops, coffee is, along with cocoa, the most commonly cultivated crops in this system. This perennial and woody plant (Bagyaraj 2015) is originated from Ethiopia, where they found grows as a natural understorey shrub of rainforest (De Beenhouwer 2014). In Indonesia, at coffee production region, they are grown under shade of canopies of trees in agroforestry system (Verbist et al 2005;Hanisch et al 2011;Evizal et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Especially high throughput sequencing technologies such as 454 amplicon pyrosequencing (Margulies et al, 2005), enabling highly efficient characterization of microbial communities by sequencing medium-sized (200-600 bp) amplicons are currently often used (e.g. Öpik et al, 2009, 2013Lekberg et al, 2012;De Beenhouwer et al, 2014). For molecular identification of AMF, the nuclear ribosomal RNA (rRNA) operon is commonly used, mainly due to its high resolving power and alignment capability across broad taxonomic groups (Stockinger et al, 2010;Schoch et al, 2012).…”
Section: Introductionmentioning
confidence: 99%